Protes Sosial Dalam Komunikasi Politik di Era Digital Melalui Civic Community Pada mahasiswa - Hidayah, Yayuk; Sapriya, Sapriya; Darmawan, Cecep; Malihah, Elly (Jurnal Studi Komunikasi, 2020)
Academics tend to not pay adequate attention to the student’s civic community, especially around its contribution to the formation of good citizens. Meanwhile, the era continues to evolve and civic student’s civic continues to change by aiming to emphasise its function as a forum for coaching students to acquire or add skills outside the classroom. This research focused on social protests in digital political communication through civic community among students. The method used in this research was qualitative phenomenology. The findings in this study indicated that social protest in digital political communication through the civic community among student has various schemes. Social media, a medium of political communication expression, has a role in providing a place to be active as an individual.